Confirmation and expansion of the phenotype of the TCEAL1-related neurodevelopmental disorder - Albuainain, Fatimah; Shi, Yuwei; Lor-Zade, Sarah; Hüffmeier, Ulrike; Pauly, Melissa; Reis, André; Faivre, Laurence; Maraval, Julien; Bruel, Ange Line; Them, Frédéric Tran Mau; Haack, Tobias B.; Grasshoff, Ute; et al. (European Journal of Human Genetics, 2024)
Numerous contiguous gene deletion syndromes causing neurodevelopmental disorders have previously been defined using cytogenetics for which only in the current genomic era the disease-causing genes have become elucidated. One such example is deletion at Xq22.2, previously associated with a neurodevelopmental disorder which has more recently been found to be caused by de novo loss-of-function variants in TCEAL1. So far, a single study reported six unrelated individuals with this monogenetic disorder, presenting with syndromic features including developmental delay especially affecting expressive speech, intellectual disability, autistic-like behaviors, hypotonia, gait abnormalities and mild facial dysmorphism, in addition to ocular, gastrointestinal, and immunologic abnormalities. Here we report on four previously undescribed individuals, including two adults, with de novo truncating variants in TCEAL1, identified through trio exome or genome sequencing, further delineating the phenotype of the TCEAL1-related disorder. Whereas overall we identify similar features compared to the original report, we also highlight features in our adult individuals including hyperphagia, obesity, and endocrine abnormalities including hyperinsulinemia, hyperandrogenemia, and polycystic ovarian syndrome. X chromosome inactivation and RNA-seq studies further provide functional insights in the molecular mechanisms. Together this report expands the phenotypic and molecular spectrum of the TCEAL1-related disorder which will be useful for counseling of newly identified individuals and their families.
CRIS-Team Scopus Importer:2024-01-19